The Influence Of The Quality Of Fiskus Services, Tax Sanctions, And The Taxpayer's Environment On Individual Taxpayer Compliance With Account Representative Professionalism As A Moderating Variable In The Pratama Batam North Tax Services Office - Basri Basri; Yuliansyah Yuliansyah; Bambang Satriawan (Pusat Riset dan Inovasi Nasional, 2023)
Individual taxpayers who carry out their obligations experience fluctuations from year to year, but there are several years that actually experience a significant decline. The level of taxpayer compliance continues to experience waves of ups and downs, so it can be said that there is instability in taxpayer compliance which shows a less good trend. The percentage shown is quite high, but actually still has not reached the maximum target. The purpose of this study was to determine and analyze the effect of service quality, tax sanctions, and taxpayer environment on taxpayer compliance directly or moderated by Account Representative Professionalism the nature of testing the relationship between variables. The research population was 67,957 individual taxpayers registered at KPP Pratama Batam Utara with sampling techniques using the Slovin formula with a leeway of 100%, a sample of 100 people was obtained. The data analysis technique uses path analysis techniques with the help of PLS Ver statistical tools 3. The results of data analysis were obtained. The quality of Fiskus services has a positive and insignificant effect on individual taxpayer compliance at KPP Pratama Batam Utara. Tax sanctions have a positive and significant effect on individual taxpayer compliance at KPP Pratama Batam Utara. The taxpayer environment has a positive and significant effect on individual taxpayer compliance at KPP Pratama Batam Utara. Professional account representatives moderate the effect of the quality of tax authorities' services positively and insignificantly on individual taxpayer compliance at KPP Pratama Batam Utara with moderation qualification is Homologizer moderator. Professional account representatives moderate the effect of tax sanctions negatively and significantly on individual taxpayer compliance at KPP Pratama Batam Utara with moderation qualification is Quasi moderator. Professional account representative moderates the influence of taxpayer environment negatively and significantly on individual taxpayer compliance at KPP Pratama Batam Utara with moderation qualification as Quasi moderator.